Fragmentation of International Human Rights Law: The problem of religious symbols in France - Céspedes Proto, Rodrigo (Derecho Público Iberoamericano, 2020)
This work examines decisions concerning religious symbols in the public space in France, including the European Court of Human Rights and the UN Human Rights Committee. At the same time, it examines the phenomenon of fragmentation of international human rights law, combining substantive and procedural legal aspects.